2018
DOI: 10.3846/aviation.2018.1855
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of the Air Transportation Market in Ukraine

Abstract: Abstract. The paper considers the current situation in the air transportation market in Ukraine. It is shown that, in the Ukrainian segment of the global aviation market, the effectiveness of passenger traffic and air transportation in reference to passenger per kilometer may grow in national and international flight routes. The authors justify the rapid increase in civil aviation efficiency and high capability of the air transport industry of Ukraine, taking into account the global rates of civil aviation dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Moreover three of the national airlines, namely "Ukraine International Airlines", "Wind rose" and "Dniproavia", are parts of a strategic alliance based on joint ownership, which allows to improve the level of services in operational activities by providing aircraft in use, assigning slots at airports, providing convenient connections of routes [28]. As it was estimated by Oleshko and Heiets [29], the share of Ukraine in the global volume of aviation passenger traffic is not significant, but "despite the instability of the military, political and economic situation in the state, the growth rate of air traffic in the Ukrainian segment of the global aviation market is optimistic for predicting the future development of air transportation in Ukraine" [29, p. 5]. This is confirmed by analysis of changes in the number of flights of domestic and foreign airlines in the airspace of Ukraine between 2015 and 2019 as well as their annual rates (Figure 3, 4), performed in this article.…”
Section: Analysis Background and Definitionsmentioning
confidence: 99%
“…Moreover three of the national airlines, namely "Ukraine International Airlines", "Wind rose" and "Dniproavia", are parts of a strategic alliance based on joint ownership, which allows to improve the level of services in operational activities by providing aircraft in use, assigning slots at airports, providing convenient connections of routes [28]. As it was estimated by Oleshko and Heiets [29], the share of Ukraine in the global volume of aviation passenger traffic is not significant, but "despite the instability of the military, political and economic situation in the state, the growth rate of air traffic in the Ukrainian segment of the global aviation market is optimistic for predicting the future development of air transportation in Ukraine" [29, p. 5]. This is confirmed by analysis of changes in the number of flights of domestic and foreign airlines in the airspace of Ukraine between 2015 and 2019 as well as their annual rates (Figure 3, 4), performed in this article.…”
Section: Analysis Background and Definitionsmentioning
confidence: 99%
“…With global economic integration, air transportation will be increasingly important in economic development [1][2]. In recent years, the whole industry of China's civil aviation has continued to develop rapidly, and the scale of a large civil aviation country has been formed [3][4][5]. In the future, China's civil aviation transportation volume will grow at an average annual rate, which puts forward higher requirements for the air transportation system and requires the construction of a more advanced civil aviation transportation information service system, which fundamentally solves the contradiction between the service guarantee capacity of each link of air transportation and the rapid growth of demand [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…When the studies in the literature are examined in the light of all this information, many studies on rail passenger transport (Baumol, 1975;Due, 1997;Jing and Yin, 2020;Kulbovskyi et al, 2019) and air passenger transport (de Oliveira Dias, 2019; Demirhan et al, 2021;Goetz, 1992;Moura et al, 2020;Oleshko and Heiets, 2018;Wolle, 2021;Yang et al, 2018) have been found. Although there are studies using different methods that examine the two modes of transport together (Albalate et al, 2015;Chen, 2017;Clewlow, 2012;Erdogan et al, 2020;Grimme, 2007;Pagliara et al,.…”
Section: Introductionmentioning
confidence: 99%